Reducing Bycatch in Aquatic Insect Sampling: Evaluating a Size-Dependent Exclusion Device for UV Light Pan Traps - Orfinger, Alexander B.; Smith, Hunter J. (Entomological Communications, 2025)
A growing body of research indicates that insect populations are declining worldwide, underscoring ongoing anthropogenic threats to biodiversity. Considering these conservation concerns, novel strategies to protect insects and other species vulnerable as bycatch to insect collecting techniques should be considered. These methods should ideally minimize bycatch while not impacting the recovery of target taxa. In the field of aquatic entomology, the UV light pan trap is widely used. While effective, this method incurs significant bycatch of unwanted arthropods and occasionally vertebrates, which both compromises the sample and has conservation implications. The goal herein was to develop and test a size-based bycatch exclusion device deployed with UV light pan traps for reducing non-target catches. This simple, cost-effective design does not require any modifications of the existing trap itself beyond adding a domed cage. "Caged" and "uncaged" traps were simultaneously deployed at two streams in northwest Georgia, USA, for a total of twelve trapping events over three months. Caddisflies (Trichoptera) served as the target taxa, namely net-spinning caddisflies (Hydropsychidae) and microcaddisflies (Hydroptilidae), and total numbers of these were counted and compared between caged and uncaged traps. No significant differences were detected between treatments. Therefore, the data suggest that these exclusion devices do not negatively impact adult caddisfly sampling and should exclude undesired large insects, such as dobsonflies, certain saturniid moths, and many vertebrates. Although these results are positive, they are preliminary, and additional questions must be addressed which are discussed in this study.